COMPARATIVE STUDY OF REACTION TIME AMONG THREE SPECIALIZED CATEGORIES OF FEMALE KHO-KHO PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
To achieve the purpose of comparing reaction time among three specialized categories of female Kho-Khoplayers viz., chasers, dodgers and all-rounder, seventy one female Kho-Khoplayers (N-71) were drawn as subjects from among the different clubs of Karnataka state and were categorized as chaser (N-22), Dodgers (N-24) and all-rounder (N-25) were selected as subjects for this study. The average age of Kho-Khoplayers who were participated in the state level tournament and their average height was 151.87 cm and their average weight was 53.50 kgs